Igal:The traditional performing arts of the bajau laut in Semporna, Sabah / Hafzan Zannie Hamza - Hafzan Zannie, Hamza (2013)
This thesis examines the concept and meaning of igal, an indigenous dance tradition of the Bajau Laut community in Semporna, Sabah. Igal or ‘dance’ to the Bajau Laut community signifies more than just a ‘dance’. This thesis posits that igal represents Bajau Laut’s culture, heritage, worldview, and cultural memory; through its epistemology and the construction of its form and content. The practice and performance of igal in Bajau Laut cultural landscape articulates the psychological impression of concept and meaning, and is signified as the Bajau Laut restored behavior. Thus, it is necessary to uncover the concept and meaning of igal through investigative studies on its practices and performances within the Bajau Laut traditional landscapes as well as stage performances. This thesis adopted Ferdinand de Saussure’s dyadic model of decoding the sign - signifier and signified; to investigate, interpret and understand the holistic conception of meaning of igal in the Bajau Laut society. This thesis also incorporated Richard Schechner’s concepts of performativity and restored behavior to elucidate the culturally structured movement system of the Bajau Laut community as a performative, symbolic and reflexive “performance.” This thesis attempts to discuss that igal as a structured movement system, is a performative expressions of an explicit and implicit coded aspect of Bajau Laut culture